Identification of potential corticosteroid binding sites on the SARS CoV-2 main protease Mpro — in silico docking study - Н. В. Хміль; А. В. Шестопалова; В. Г. Колесніков; А. О. Боєчко-Немовча (Біофізичний вісник)
Background: Currently, an increase in the number of new cases of Covid-19 caused by the severe acute respiratory syndrome virus (SARS-CoV-2) is recorded in Ukraine and the world. SARS-CoV-2 provokes exacerbation of chronic diseases and activates inflammatory and allergic reactions. A severe course of Covid-19 increases the duration of hospitalization and the mortality rate among the population. Pathogenetic therapy is carried out with systemic corticosteroids, which suppress the cytokine storm by mitigating the SARS-CoV-2-induced systemic inflammatory response and inhibit SARS-CoV-2 main protease Mpro, a key component of viral replication.